A narrative review of the effect of parent–child shared reading in preterm infants - Boissel, Laure; Guilé, Jean-Marc; Viaux-Savelon, Sylvie; Mariana, Charlotte; Corde, Pascal; Wallois, Fabrice; Benarous, Xavier (Frontiers in Pediatrics, 2022)
The benefits of book-reading interventions on language development in full-term infants have been well investigated. Because children born preterm face a greater risk of cognitive, language and emotional impairments, this narrative review examines the theoretical evidence, empirical findings, and practical challenges for introducing such intervention to this population. The effect of shared book interventions on typically developing infants is mediated by three components: a linguistic aspect (i.e., exposure to enriched linguistic input), an interactive aspect (i.e., eliciting more synchronous and contingent communication), and a parental aspect (i.e., reducing parental stress and increasing sense of control). Parental shared book reading in a neonatal intensive care unit (NICU) was found to be feasible and well accepted. It provides concrete support for positive parenting in a highly stressful context. Preliminary evidence supports a positive effect of shared reading sessions in physiological parameters of preterm infants in NICU. One study showed that parental shared book reading in an NICU is associated with lower decline in language development during the first 24 months compared to a historical control group. Findings from a community-based birth cohort confirm the positive effect of this intervention on cognitive development with a 2-year-follow up. More structured clinical trials are now needed to confirm these preliminary findings. Questions remain about possible moderators of these interventions, in particular cultural features.